Osteochondral Lesions of the Ankle and Foot - Haug, Logan P.; Sill, Andrew P.; Shrestha, Roman; Patel, Karan A.; Kile, Todd A.; Fox, Michael G. (Seminars in Musculoskeletal Radiology, 2023)
Osteochondral lesions (OCLs) in the ankle are more common than OCLs of the foot, but both share a similar imaging appearance. Knowledge of the various imaging modalities, as well as available surgical techniques, is important for radiologists. We discuss radiographs, ultrasonography, computed tomography, single-photon emission computed tomography/computed tomography, and magnetic resonance imaging to evaluate OCLs. In addition, various surgical techniques used to treat OCLs—debridement, retrograde drilling, microfracture, micronized cartilage-augmented microfracture, autografts, and allografts—are described with an emphasis on postoperative appearance following these techniques.
Keywords: osteochondral lesion; talus; ankle; foot; magnetic resonance imaging